The China Experience as a Contribution for a New Economic Paradigm (The Macau Ricci Institute Journal, 2020)
YanINTRODUCTIONPope Francis has called for a change in the current economic paradigm, taking into account integral human development. With the current crisis of the pandemic, climate change, and global recession, China is foreseen to be one of the very few countries that register a positive economic growth this year. With the sheer size of her economy and her own characteristics, China does not pretend that her development model could be an example for other countries. However, there may be something that the China experience could inspire in us. Therefore, in this paper, I would like to focus some points for consideration.